The pathological aesthetics of design: examining repression and perverse representation in contemporary visual culture from the perspective of psychoanalytic theory - Jiang, Xinyan (Frontiers in Communication, 2025)
This article explores the pathological aesthetics of design by examining the repression and perverse representations in contemporary visual culture through the lens of psychoanalytic theory. It traces the origins of repression and perversion in visual culture to the context of modernity, characterized by visual centrism, consumer society, and technological innovations. The article then interprets visual culture using key concepts from psychoanalytic theorists such as Freud, Lacan, and Deleuze, revealing the pathological manifestations of repressed desires and perverse imaginaries in various design practices, including advertising, movie posters, and social media. Finally, it proposes a transformative vision for design aesthetics, one that confronts repression, challenges perversion, and embraces a more diverse, inclusive, and humanistic approach to design ethics and aesthetics. The article concludes by reflecting on the critical mission of visual culture criticism and design aesthetics in guiding healthy and responsible design practices.